Factors that affect the performance of the state civil apparatus - Maryani Maryani; Arifani Arifani; Djafar Djafar (Jurnal Inovasi Ekonomi, 2021)
This study explains the influence and causal relationship between exogenous and endogenous variables based on the research framework. The population in this study is the employees of the Regional Secretariat of the Provinces of South Sulawesi and West Sulawesi, with a total of 40 respondents who are used as research samples, and the analysis was performed by multiple linear regression. This study found that education and training, organizational culture, facilities and infrastructure, and regulations simultaneously significantly influence financial management performance.